2013
DOI: 10.2754/avb201382030317
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes of mucous membrane and the presence of immunoglobulins in small intestines of neonatal pigs

Abstract: The structure of the small intestine of neonatal pigs has an important effect on immunoglobulin absorption. The aim of the experiment was to observe changes in the mucous membrane and the presence of immunoglobulins in the intestines of piglets during the first hours of their postnatal lives. In total, 80 piglets of the Large White breed were divided into two groups of 40 pigs. One group (control) came from an infection-free breeding, the other (experimental) group came from a breeding with the reproduction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…From this point of view, the transport of immunoglobulin from colostrum to piglet blood during period of colostrum nutrition must be as high as possible. Kanka et al [2013Kanka et al [ , 2014 found out positive correlation between concentration of immunoglobulins in sow's colostrum and presence of immunoglobulins in small intestine of piglets, as well as between presence of immunoglobulins in small intestine of piglets and concentration of immunoglobulins in blood of piglets. Therefore, the concentration of immunoglobulins in colostrum is especially important and must be as high as possible.…”
Section: Immunoglobulinsmentioning
confidence: 99%
“…From this point of view, the transport of immunoglobulin from colostrum to piglet blood during period of colostrum nutrition must be as high as possible. Kanka et al [2013Kanka et al [ , 2014 found out positive correlation between concentration of immunoglobulins in sow's colostrum and presence of immunoglobulins in small intestine of piglets, as well as between presence of immunoglobulins in small intestine of piglets and concentration of immunoglobulins in blood of piglets. Therefore, the concentration of immunoglobulins in colostrum is especially important and must be as high as possible.…”
Section: Immunoglobulinsmentioning
confidence: 99%
“…Simplified methods • Graphic-numerical index method, [1] • Operational method, [2] • The method of searching values in tables, [2] Complex methods • Technical method resp. method of G. B. Watters s with modifications used by software NEPruzvucnost, [3] • Predictions based on CSN 12354-1with relations according to S. Faha.…”
Section: Introductionmentioning
confidence: 99%